cAMP signaling by anthrax edema toxin induces transendothelial cell tunnels, which are resealed by MIM via Arp2/3-driven actin polymerization - Maddugoda, Madhavi P; Stefani, Caroline; Gonzalez-Rodriguez, David; Saarikangas, Juha; Torrino, Stéphanie; Janel, Sebastien; Munro, Patrick; Doye, Anne; Prodon, François; Aurrand-Lions, Michel; Goossens, Pierre L; Lafont, Frank; et al. (Cell host & microbe, 2011)
RhoA-inhibitory bacterial toxins, such as Staphylococcus aureus EDIN toxin, induce large transendothelial cell macroaperture (TEM) tunnels that rupture the host endothelium barrier and promote bacterial dissemination. Host cells repair these tunnels by extending actin-rich membrane waves from the TEM edges. We reveal that cyclic-AMP signaling produced by Bacillus anthracis edema toxin (ET) also induces TEM formation, which correlates with increased vascular permeability. We show that ET-induced TEM formation resembles liquid dewetting, a physical process of nucleation and growth of holes within a thin liquid film. We also identify the cellular mechanisms of tunnel closure and reveal that the I-BAR domain protein Missing in Metastasis (MIM) senses de novo membrane curvature generated by the TEM, accumulates at the TEM edge, and triggers Arp2/3-dependent actin polymerization, which induces actin-rich membrane waves that close the TEM. Thus, the balance between ET-induced TEM formation and resealing likely determines the integrity of the host endothelium barrier.